What Green Finance Does Indonesia after COVID 19? - Heny Handayani (Jurnal Mirai Management, 2023)
The goal of this study is to learn more about how green finance has affected Indonesia since COVID-19. This research methodology combines qualitative inquiry with the technical documentation of data collecting. This study comes to the conclusion that a country's regulatory framework can be strengthened or investment in clean and green technologies increased to boost green financing. The country is dedicated to creating a balanced and sustainable Indonesia, under the National Long-Term Development Plan (RPJPN), by enhancing the economic utilisation of the environment and natural resources in a sustainable way. The nation is also committed to improving environmental and natural resource management in order to raise peoples' standards of living.